Quaternary climatic oscillations shaped the demographic history and triggered intraspecific divergence of Rhododendron shanii, a mid-montane endemic in eastern Asia - Deng, Yong; Li, Zhen; Hu, Yingfeng; Li, Zhizhong; Zhang, Siyu; Liu, Kun; Shao, Jianwen (Frontiers in Plant Science, 2026)
Mountainous regions often serve as critical biodiversity hotspots. In mid-altitude mountains, populations may be more vulnerable to climate-driven fluctuations than those in alpine regions due to limited capacity for elevational range shifts. However, empirical studies on how past climatic changes shaped the demographic history of organisms in the mid-mountains remain scarce, particularly those utilizing genomic data. Here, we conducted population genomic analyses of Rhododendron shanii, an endemic species in the Dabie Mountains of eastern Asia. Combined with species distribution modeling, our demographic analyses indicate that this species underwent glacial expansion during Quaternary cooling periods but experienced three distinct population bottlenecks over the past 0.4 million years, all coinciding with interglacial warm periods. Its population size has continuously declined throughout the Holocene as temperatures rose. Significant genetic differentiation has occurred among populations inhabiting different mountaintops despite their highly restricted distribution. Notably, warm conditions during the last interglacial period (0.12–0.13 Mya) triggered the divergence between the southern lineage (S: TJ, SBG, DZJ) and the northern lineage (N: THJ, BMJ, DYJ). Compared to closely related species, R. shanii currently exhibits a high inbreeding rate yet maintains relatively high genetic diversity and low genetic load. This unique genetic signature is likely linked to its recent rapid population contraction. Collectively, our findings demonstrate how Quaternary climatic oscillations and mid-mountain topography shaped the demographic trajectories and genomic landscape of R. shanii, providing new insights into the formation and vulnerability factors of biodiversity within mid-elevation sky island systems under global warming scenarios.